Risk Factors Causing Occupational Accidents Using the FMEA and Fishbone Methods in the Particle Board Division of PT. Kutai Timber Indonesia - Trismawati; Nadia Putri; Haryono; Tri Prihatiningsih (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
Occupational Health and Safety (OHS) is an essential aspect of industrial operations, aimed at preventing workplace accidents and maintaining a safe and productive environment. The Particle Board Division of PT. Kutai Timber Indonesia faces high accident risks due to heavy machinery and high-temperature processes. This study evaluates potential occupational hazards using the Failure Mode and Effects Analysis (FMEA) and Fishbone Diagram methods. FMEA is used to prioritize risks based on the Risk Priority Number (RPN), while the Fishbone Diagram identifies the root causes of critical hazards. The highest identified risk is the absence of an emergency response team in each shift (RPN = 148.5). Other major risks include inadequate monitoring of corrective actions, poor documentation systems, low employee involvement in hazard identification, and insufficient technical controls. Recommendations include forming emergency response teams, conducting regular safety training, improving documentation systems, and enhancing technical and administrative controls. Implementing these measures is expected to reduce accident rates and strengthen the safety culture in the company.